KORELASI WAKTU REAKSI DAN AKSELERASI TERHADAP PRESTASI LARI 100 METER MAHASISWA PUTRA SEMESTER II PROGRAM STUDI PENJASKESREK FKIP UNIVERSITAS RIAU - Yuherdi, Yuherdi; Wijayanti, Ni Putu Nita; Pratiwi, Mentari (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2013)
Problems in the research starts from the observation that researchers encountered in the field that theability of students in running 100 meters was not so good because it was allegedly affected byacceleration and reaction time. The purpose of this research is to know the relation between reactionand accelerated time towards the achievement of male students on running 100 meters in the secondsemester Penjaskesrek FKIP UR. This type of research is correlasional. The population in thisresearch is 76 male students in the second semester Penjaskesrek FKIP UR using purposive samplingtechnique, and then the sample on this research is 35 male students. Whole Body Reaction Test is usedtp get the data, running 30 meters and 100 meters run test. The Data obtained were analyzed withsimple and double product moment. Based on the analysis of the data it was found that there was asignificant relationship between the reaction time and running 100 meters, marked by the resultsobtained were r.count 0.465 > r.table 0,334, then there was a significant relationship betweenaccelerated and 100 meters, marked by the results obtained were r.count 0,434 > r.table 0,334, andthere was a significant relationship between reaction time and accelerated toward the achievement ofmale students on running 100 meters in the second semester Penjaskesrek FKIP UR, was marked bythe results obtained R.count 0,562 > Rtabel 0,334.Key Words: Reaction Time, Acceleration, running 100 meters.